Nutritional Composition and Lipid Oxidation Stability of Beef Patties Packed with Biodegradable and Non-Biodegradable Materials (Kestabilan Komposisi Makanan dan Pengoksidaan Lemak Burger Daging yang Dibungkus dengan Bahan Mudah Urai dan Tidak Mudah Urai Secara Biologi) - Lim, S. L .; Wan Rosli, W. I. (Faculty of Science and Technology, Universiti Kebangsaan Malaysia, 2014)
Long term environmental problems of non-biodegradable plastic, the need to conserve finite fossil fuels and the impact of globalization of food supply are some of the driving forces in looking towards biodegradable plastics as an alternative to the existing petrochemical-based polymers for food packaging application. The stability of nutritional composition, lipid oxidation, physical traits of beef patties packed with different types of plastics and the surface morphology of plastics after 3 months of frozen storage (-18 were studied. Beef patties were packed with either non-biodegradable high density polyethylene (PE), hydro-biodegradable low density polyethylene/thermoplastic sago starch plastic (PES), hydro-biodegradable polylactic acid plastic (PLA) or oxo-biodegradable plastic (OXO)). There were no differences in most of the nutrients analyzed and lipid oxidation values of beef patties packed with either biodegradable or non-biodegradable plastics after storage. There were significant (p decreased in fat for cooked patties and moisture for both raw and cooked patties. Lipid oxidation indices of beef patties increased after storage but they were not significant (p Beef patties packed with biodegradable packaging materials were able to retain moisture without jeopardizing the diameter reduction during storage. In summary, the application of biodegradable plastics for packing beef patties was considered acceptable and can be suggested as an alternative packaging item to replace conventional polyethylene plastic packaging. || Masalah berpanjangan akibat penggunaan plastik tidak terbiodegradasi, keperluan untuk memelihara bahan api fosil yang terhad serta impak daripada globalisasi bekalan makanan merupakan antara pendorong utama dalam menggantikan plastik petrokimia yang sedia ada dengan plastik terbiodegradasi dalam sektor pembungkusan makanan. Kestabilan komposisi pemakanan, pengoksidaan lemak, sifat fizikal burger daging yang dibungkus dengan plastik yang berlainan serta morfologi permukaan plastik selepas 3 bulan penyimpanan beku (-18 telah dikaji. Burger daging dibungkus sama ada dengan polietilena jenis ketumpatan tinggi yang tidak terbiodegradasi (PE), plastik hidro-terbiodegradasi polietilena jenis ketumpatan rendah/termoplastik kanji sago (PES), plastik hidro-terbiodegradasi asid polilaktik (BPLA) atau plastik oxo-terbiodegradasi (OXO)). Tidak ada perbezaan yang ketara dalam corak perubahan dalam kebanyakan nutrien yang dianalisis dan nilai pengoksidaan lemak burger daging yang dibungkus dengan plastik tidak terbiodegradasi atau plastik terbiodegradasi selepas tempoh penyimpanan. Terdapat penurunan yang ketara (p < 0.05 untuk lemak dalam burger masak dan kelembapan untuk kedua-dua burger mentah dan masak. Nilai pengoksidaan lemak burger meningkat selepas tempoh penyimpanan tetapi ia tidak ketara (p > 0.05 Burger daging yang dibungkus dengan plastik terbiodegradasi mampu mengekalkan kelembapan tanpa memudaratkan pengurangan diameter semasa penyimpanan. Kesimpulannya, aplikasi pembungkusan plastik terbiodegradasi untuk burger daging dapat diterima dan boleh dicadangkan sebagai pembungkus alternatif bagi menggantikan pembungkusan plastik polietilena konvensional.